Penerapan Komunikasi Antarbudaya Dai dan Daiyah dalam Berdakwah di Aceh - Ade Irma (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Intercultural communication cannot be avoided in communication process, including in da’wah. Dai (man preacher) and daiyah (woman preacher), whether they realize it or not, have practiced intercultural communication in their da'wah activities. There are important parts in intercultural communication that can cause success or failure in delivering da'wah. One important part is that dai and daiyah recognize their mad'u culture. Unfortunately, we still find dai and daiyah who have not implemented intercultural communication by taking into account mad'u's cultural differences when preaching, causing mad'u to be less enthusiastic and even no longer willing to attend da'wah studies. Researchers used qualitative methods. In an effort to obtain information related to this, the researcher interviewed mad'u in depth, who is a young intellectual who often participates in religious studies, both on campus, outside campus and at the mosque. The results of data mining from informants found that we still found, 1) dai and daiyah who preach by equating or assuming that every mad'u is the same without realizing that the mad'u present come from diverse cultures, 2) dai and daiyah who stereotype to their mad'u, 3) dai and daiyah who are less sensitive and misinterpret mad'u's nonverbal messages, 4) dai and daiyah who are less able to adjust their language when preaching, 5) dai and daiyah who negatively assess the differences between themselves and mad 'u.